(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2015)
The starting point for tackling the issue of moral damages in the face of INSS acts will be the constitutional text. As is well known, in the contemporary conception of constitutionalists, every interpretation of the law is a constitutional interpretation, given the principiological and programmatic supremacy of the values enshrined therein. In this regard, in view of the uniform interpretation of constitutional provisions, it is important to emphasize that the granting or denial of social security benefits must be supported by the fundamental rights standard: human dignity and all the other values that stem from it. In the case under discussion, the importance of isonomy; the social function of property; the commitment to eradicate poverty and marginalization; due process of law; the social right to assistance for the destitute and social security - which will be materialized through universal coverage and social security care - are highlighted from an axiological point of view. It is also imperative to base the issue on the constitutional requirement to conform administrative acts to the guidelines of legality and efficiency - with the specifications brought in by Law No. 9.784/1999 - especially in the arena of a managerial administration, whose public service must be subjected to the sieve of periodic quality assessment. It should be emphasized that quality in the public social security service is important because the benefits offered to the insured are of a high quality.